Effect of match‐run frequencies on the number of transplants and waiting times in kidney exchange. Issue 5 (5th December 2017) - Ashlagi, Itai; Bingaman, Adam; Burq, Maximilien; Manshadi, Vahideh; Gamarnik, David; Murphey, Cathi; Roth, Alvin E.; Melcher, Marc L.; Rees, Michael A.
Abstract : Numerous kidney exchange (kidney paired donation [KPD]) registries in the United States have gradually shifted to high‐frequency match‐runs, raising the question of whether this harms the number of transplants. We conducted simulations using clinical data from 2 KPD registries—the Alliance for Paired Donation, which runs multihospital exchanges, and Methodist San Antonio, which runs single‐center exchanges—to study how the frequency of match‐runs impacts the number of transplants and the average waiting times. We simulate the options facing each of the 2 registries by repeated resampling from their historical pools of patient‐donor pairs and nondirected donors, with arrival and departure rates corresponding to the historical data. We find that longer intervals between match‐runs do not increase the total number of transplants, and that prioritizing highly sensitized patients is more effective than waiting longer between match‐runs for transplanting highly sensitized patients. While we do not find that frequent match‐runs result in fewer transplanted pairs, we do find that increasing arrival rates of new pairs improves both the fraction of transplanted pairs and waiting times. Abstract : Data‐driven simulations of the matching frequency employed by kidney exchange registries reveal that frequent match runs do not result in fewer transplanted patients, while increasing arrival rates of new pairs improves both the fraction of transplanted pairs and waiting times.